CAPACITANCE MONITORING SYSTEM FOR ELECTROSTATIC WIND ENERGY HARVESTER - Aljadiri, Rita T; Taha, Luay Y; Ivey, Paul (MATTER: International Journal of Science and Technology, 2015)
In this paper, a capacitance monitoring system for electrostatic wind energy harvesters has been proposed. First, the operation of the harvester and the harvesting cycle is explained in details. Second, the capacitance monitoring system is demonstrated. Third the simulation and experimental testing of the monitoring system is presented. The capacitance monitoring system requires a microcontroller to sense the change in capacitance and to provide controlling signals to operate the harvester during the harvesting cycle. Results of the testing proved successful operation of the monitoring system in detecting capacitance variation with time